INFLUENCE OF PRINCIPALS’ AUTOCRATIC LEADERSHIP STYLES ON TEACHER MOTIVATION IN PUBLIC SECONDARY SCHOOLS IN KAKAMEGA NORTH SUB-COUNTY, KENYA - Sasaka, Marygorret; Omusula, Christopher; Kibanani Ngome, Charles (Journal of Advance Research in Social Science and Humanities (ISSN 2208-2387), 2022)
The purpose of this study was to assess the influence of principals’ autocratic leadership styles on teacher motivation in public secondary schools in Kakamega North sub-county. The study was based on path-goal and motivational theory. The study adopted descriptive survey research design with a target population of 1164 persons; that comprised of 52 Secondary School Principals and 1112 teachers. A sample size of 454 persons, that consisted of 32 Principals and 422 teachers. Stratified random sampling technique was used to identify the respondents. Questionnaires were the main data collection tools that were used in the study. Reliability of the instrument was determined through a pilot study in some selected public secondary schools in Kakamega East Sub-County. The reliability index for Principals’ questionnaire was 0.768 while that for teachers’ questionnaire was 0.713. Descriptive (percentages and mean) and inferential statistics (chi-square test) were used in the analysis of quantitative data and was presented in tables. The study established that there were significant relationships between use of unilateral decision making, (?2 (1) = 98.33, p<.003,), emphasis on assertiveness in working relationships (?2 (1) = 76.94, p<.003,); status and power building among staff (?2 (1) = 58.62, p<.041,) and emphasis on rigorousness in work (?2 (1) = 85.24, p<.033) and teacher motivation in public secondary schools in Kakamega North sub-county, Kenya. The study is significant in that it can be used by policy makers in the education sector to inform the development of policies and strategies aimed at improving teacher motivation.